(untitled) (Baghdad Science Journal, 2008)
In this paper, Bernstein polynomials method has used to find an approximate solution for Fredholm integral equation of the second kind. These polynomials are incredibly useful mathematical tools, because they are simply defined, can be calculated quickly on computer systems and represent a tremendous variety of functions. They can be differentiated and integrated easily.